2017
DOI: 10.3390/nu9050521
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Probiotic Bacteria

Abstract: Oxidative stress defines a condition in which the prooxidant–antioxidant balance in the cell is disturbed, resulting in DNA hydroxylation, protein denaturation, lipid peroxidation, and apoptosis, ultimately compromising cells’ viability. Probiotics have been known for many beneficial health effects, and the consumption of probiotics alone or in food shows that strain-specific probiotics can present antioxidant activity and reduce damages caused by oxidation. However, the oxidation-resistant ability of probioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
436
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 684 publications
(460 citation statements)
references
References 134 publications
(155 reference statements)
11
436
0
13
Order By: Relevance
“…The elimination of free radicals by probiotics is one of the probable protective mechanisms against hepatic intoxication and the consequent decrease in the serum levels of AST, ALT, ALP, GGT creatinine and urea observed in the present study. Studies indicate that probiotic bacteria are able to raise the efficiency of the host's antioxidant system and thus decrease the formation of free radicals . Similar results have been reported in studies in rats poisoned with Acetaminophen and treated with the probiotic Enterococcus lactis , and also in rats with adenine‐induced renal failure and treated with Lactobacillus casei Shirota…”
Section: Discussionsupporting
confidence: 76%
“…The elimination of free radicals by probiotics is one of the probable protective mechanisms against hepatic intoxication and the consequent decrease in the serum levels of AST, ALT, ALP, GGT creatinine and urea observed in the present study. Studies indicate that probiotic bacteria are able to raise the efficiency of the host's antioxidant system and thus decrease the formation of free radicals . Similar results have been reported in studies in rats poisoned with Acetaminophen and treated with the probiotic Enterococcus lactis , and also in rats with adenine‐induced renal failure and treated with Lactobacillus casei Shirota…”
Section: Discussionsupporting
confidence: 76%
“…Thus, the microbiota-targeted dietary and probiotic interventions are benefit for host health via modulating nutrition metabolism, ameliorating immune homeostasis, and facilitating antioxidative capacity (42). Increasing evidence shows that probiotics, especially lactobacilli and bifidobacterium, exert important roles in reducing accumulation of ROS and improving antioxidation activities in the host (8,9). Here, we first reported that L. frumenti can fortify the antioxidant capacity via NOS1 activation in jejunal PRDXs are antioxidant enzyme family that can remove free radicals (30).…”
Section: Discussionmentioning
confidence: 93%
“…Growing evidence has demonstrated that probiotics can regulate gastrointestinal functions and have various beneficial effects on the host (7). Interestingly, recent studies have also suggested that probiotics (including Lactobacillus rhamnosus, Bifidobacterium animalis, and Lactobacillus plantarum) exhibit antioxidant properties on the host and have emerged as potential antioxidants (8,9). We have previously reported that Lactobacillus frumenti strain is a main intestinal Lactobacillus in weaned piglets (10).…”
mentioning
confidence: 99%
“…There have been studies that rigorously characterize the effect of probiotics on antioxidation regarding the intestinal microbiota composition. Probiotics may modulate the redox status of the host via their metal ion chelating ability, antioxidant systems, regulating signalling pathways, enzyme producing ROS and intestinal microbiota . In addition to the above mechanisms, intestinal microflora can also increase the level of nitric oxide through nitrate reduction in the non‐enzymatic pathway .…”
Section: The Role Of Gut Microbiota In Cardiovascular Diseasementioning
confidence: 99%
“…Probiotics may modulate the redox status of the host via their metal ion chelating ability, antioxidant systems, regulating signalling pathways, enzyme producing ROS and intestinal microbiota. 96 In addition to the above mechanisms, intestinal microflora can also increase the level of nitric oxide through nitrate reduction in the non-enzymatic pathway. 39 At the same time, changes in the structure of GM, also affect the expression and activity of some other molecules acting on the blood such as the AMPactivated protein kinase, hypoxia-inducible factor-1α and peroxisome proliferator-activated receptorγ coactivator-1α.…”
Section: The Role Of G Ut MI Crob I Ota In C Ardiova Scul Ar Dis E mentioning
confidence: 99%